2002
DOI: 10.1007/bf03186089
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cold rolling parameters on sagging behavior for three layer Al−Si/Al−Mn(Zn)/Al−Si brazing sheets

Abstract: The effects of intermediate annealing (IA) and the final cold rolling (CR) condition on the microstructure and sagging resistance during brazing were investigated using three layer clad sheets composed of the Al-7.5 wt.%Si alloy (filler, thickness: 10 μm)/Al-1.3 wt.%Mn based alloy (core, 80 μm)/Al-7.5 wt.%Si alloy (filler, 10 μm). Also, the effect of 1.2~2 wt.% Zn addition into the core on the sagging resistance of the clad sheets was determined. It was revealed that all the clad sheets fabricated by the optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In the manufacturing of heat exchangers, it is necessary that the fin material maintain a certain mechanical strength at a maximum brazing temperature of about 600 • C in order to prevent sagging and deformation, or even cracking during brazing [6,7]. At such high temperatures, aluminum alloys will inevitably undergo phenomena such as recovery, recrystallization, grain growth, second phase particle growth, particle redissolution, intergranular erosion, and slip deformation at grain boundaries, leading to a sharp decline in their mechanical properties [6][7][8][9][22][23][24]. On the other hand, grain boundaries show viscosity at high temperatures, which greatly reduces the resistance to deformation [25].…”
Section: The Influence Of Alloying On the Mechanical Properties Of Al...mentioning
confidence: 99%
“…In the manufacturing of heat exchangers, it is necessary that the fin material maintain a certain mechanical strength at a maximum brazing temperature of about 600 • C in order to prevent sagging and deformation, or even cracking during brazing [6,7]. At such high temperatures, aluminum alloys will inevitably undergo phenomena such as recovery, recrystallization, grain growth, second phase particle growth, particle redissolution, intergranular erosion, and slip deformation at grain boundaries, leading to a sharp decline in their mechanical properties [6][7][8][9][22][23][24]. On the other hand, grain boundaries show viscosity at high temperatures, which greatly reduces the resistance to deformation [25].…”
Section: The Influence Of Alloying On the Mechanical Properties Of Al...mentioning
confidence: 99%
“…Composed of support layer (core layer) and brazing layer (clad layer), multilayer aluminum brazing sheets have been widely used in heat exchanger and honeycomb sandwich structure [1] due to their low density, high thermal conductivity, and excellent corrosion resistance [2][3][4][5]. In order to reduce the weight of automotive parts and cut down production cost of the heat exchanger, the thickness of the Al brazing sheet has to be decreased [6].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Qin et al [8] observed that the value of sagging of the brazed foil sheet had undergone two stages of change as a function of temperature, and the sagging was attributed to dissolution of precipitates and softening of elastic modulus as a function of brazing temperature. Lee et al [2,3] studied the sagging behavior of three-layered (Al-Si/Al-Mn-Zn/Al-Si) clad sheets and found that coarse recrystallized grains can improve sagging resistance. is type of microstructure can be obtained by controlling the rate of cold-rolling reduction and applying an intermediate annealing temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The grain structure of the fin during brazing is an influential factor in controlling the brazeability. Previous studies have reported the recrystallization behavior of the grain structure during brazing heat treatment [2][3][4][5]. Limited erosion was shown due to coarsely recrystallized grain structure during brazing in cladded Al-Mn alloys [2].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported the recrystallization behavior of the grain structure during brazing heat treatment [2][3][4][5]. Limited erosion was shown due to coarsely recrystallized grain structure during brazing in cladded Al-Mn alloys [2]. The addition of Ni in Al-Fe-Mn-Si alloy improved brazeability with a larger recrystallized grain structure [3].…”
Section: Introductionmentioning
confidence: 99%